A morbid taste for bones eaudiobook - Peters, Ellis (The Chronicles of Brother Cadfael, 2014)
On an expedition to acquire a saint's remains, Brother Cadfael instead finds intrigue and murder It is 1137, and the ambitious head of the Shrewsbury Abbey wishes to acquire the remains of Saint Winifred for the glory of his Benedictine order. Brother Cadfael is part of the expedition sent to the saint's final resting place in Wales, where he finds the villagers divided over the Benedictines' quest. When the leading opponent to moving the grave is shot dead with a mysterious arrow, some believe Winifred herself delivered the blow. Brother Cadfael knows that an earthly hand did the killing. But he doesn't know that his plan to root out a murderer may dig up a case of love and justice, where the waves of sin may be scandal—or his own ruin.